PEMBERDAYAAN PETANI IKAN LELE MELALUI PENYULUHAN DAN PELATIHAN VAKSINASI HYDROVAC - Dian Tariningsih (Universitas Teuku Umar, 2019)
The maintenance of catfish conducted by the catfish culture group in Kusamba Village still faces various obstacles, namely the high mortality rate of catfish seeds during the maintenance process. Knowledge and skills of farmers about catfish farming technology are not enough to be able to overcome the problems faced. The objectives of community empowerment are (1) to increase farmers' knowledge and skills about hydroVac vaccination, (2) to increase the survival rate of catfish through hydroVac vaccination technology innovation. The implementation of the community empowerment program uses the Technology Transfer (TT) approach. through counseling, training, and a demonstration of the hydroVaac vaccination application. Farmers' knowledge and skills are measured on a scale of three. The results of this community empowerment show that (1) the level of knowledge and skills of farmers increased after being given counseling and training in hydroVac vaccination. (2) Innovation of hydroVac vaccination technology can increase the survival rate of catfish.